Research Review: The effects of mindfulness‐based interventions on cognition and mental health in children and adolescents – a meta‐analysis of randomized controlled trials. (22nd October 2018) - Dunning, Darren L.; Griffiths, Kirsty; Kuyken, Willem; Crane, Catherine; Foulkes, Lucy; Parker, Jenna; Dalgleish, Tim
Abstract : Background: Mindfulness based interventions (MBIs) are an increasingly popular way of attempting to improve the behavioural, cognitive and mental health outcomes of children and adolescents, though there is a suggestion that enthusiasm has moved ahead of the evidence base. Most evaluations of MBIs are either uncontrolled or nonrandomized trials. This meta‐analysis aims to establish the efficacy of MBIs for children and adolescents in studies that have adopted a randomized, controlled trial (RCT) design. Methods: A systematic literature search of RCTs of MBIs was conducted up to October 2017. Thirty‐three independent studies including 3, 666 children and adolescents were included in random effects meta‐analyses with outcome measures categorized into cognitive, behavioural and emotional factors. Separate random effects meta‐analyses were completed for the seventeen studies ( n = 1, 762) that used an RCT design with an active control condition. Results: Across all RCTs we found significant positive effects of MBIs, relative to controls, for the outcome categories of Mindfulness, Executive Functioning, Attention, Depression, Anxiety/Stress and Negative Behaviours, with small effect sizes (Cohen's d ), ranging from .16 to .30. However, when considering only those RCTs with active control groups, significant benefits of an MBI were restricted to the outcomes of Mindfulness ( d = .42), Depression ( d = .47) and Anxiety/Stress ( d = .18) only. Conclusions: This meta‐analysis reinforces the efficacy of using MBIs for improving the mental health and wellbeing of youth as assessed using the gold standard RCT methodology. Future RCT evaluations should incorporate scaled‐up definitive trial designs to further evaluate the robustness of MBIs in youth, with an embedded focus on mechanisms of action.